Two neonates with annular lesions of the face. - García-Montero, P.P.; González-Olivares, M.; Rojas-Mora, E.; Echeverria-García, B.; Martínez-Morán, C.; Tardío, J.C.; Borbujo, J. (European Journal of Pediatric Dermatology, 2016)
Two newborns with annular lesions of the face were reported. Neonatal lupus erythematosus was ruled out thanks to laboratory examinations. Mycological cultures grew Trichophyton mentagrophytes in the first case and Microsporum canis in the second. In spite of the involvement of the hair the lesions healed with only topical treatment.